Microfossils of the Guadalupe group and the Guaduas formation (campaniano-maastrichtlano) in the Tausa section, Cundinamarca, Colombia. - MARTÍNEZ , J. l. (CT&F - Ciencia, Tecnología y Futuro, 1995)
A rich assemblage of foraminifers and ostracods recovered from the Guadalupe group and the base of the Guaduas formation in the Tausa section are described and illustrated. The Guadalupe group is characterized by a low microfounal diversity dominated by the buliminids Siphogenerinoides ewaldi and Siphogenerinoides bramlettei. lncrements in microfoaunal diversity appear to correspond to the middle part of Transgressive System Tracts. Siphogenerínoides bramlettei (lote Maastrichtion in age) supersedes Síphogenerinoides ewaldi (lote Camponion in age); the occurrence of the two taxa corresponds to the first sequence boundary in the Ploeners formation of the Guadalupe group. The first occurrence of S. bramlettei appears to be "isochronous" in northern South America. The base of the Guaduas formation is characterized by a high diversity of calcoreous benthonic foraminifera (rotaliids). Microfossils from the Guadalupe group and Guaduas formation were affected by two taphonomic processes: (1) kaolinite infilling previous to dissolution of tests during the mesodiogenetic stage, and (2) pyrite infilling and pyritization (in sulfidic microenvironments) previous to dissolution of tests during the eodiogenefic stage.